A method for preparing gold-encapsulated nanometer highly conductive material
By using specific additives and frozen treatment during the mixing process of graphene and metal, and multiple melting stirring circulation, the problem of carbonization and gathering during the mixing process of graphene and metal is solved. High -conductive performance and uniformity.
Patent Information
- Application Number
- CN202410544653.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-06
AI Technical Summary
In the prior art, carbonization and agglomeration are easily generated during the mixing and melting of graphene and metal, resulting in less obvious performance and effect.
Use dried oxygen oxygenne powder, aluminum powder, and metal powder, and add potassium fluoropromothalox, potassium fluoroplasm, ethylene glycol, alcohol, and amopic ether under anaerobic conditions for mixing. And multiple melting stirring circulation to promote the uniform dispersion and adsorption of graphene.
Through this method, graphene showed better conductive performance and uniformity in the hyper -conductive material of the hyper -gold nano -nano -nano -high electrical material, significantly improved the conductive performance of the material.
Smart Images

Figure CN118291806B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphene metal materials, and in particular relates to a method for preparing a graphene gold nanometer highly conductive material. Background Art
[0002] At present, it is difficult to manufacture products with graphene as a single material. It is mainly to use its outstanding characteristics to combine with other material systems to prepare new composite materials, so that graphene-based composite materials have many excellent properties. For example, using graphene as a carrier to load nanoparticles can improve the catalytic and conductive properties of these particles; adding it to polymers can improve the mechanical and thermal conductivity of the material.
[0003] In the prior art, graphene is used as a surface penetration method, or as a surface coating method, or by direct addition or mixed addition. In this process, it is very difficult to control the uniformity of graphene, and the performance effect of using unprocessed graphene is not very obvious. Graphene is a two-dimensional nanomaterial. By synthesizing graphene with aluminum powder, ball milling, sintering and other powder metallurgy technologies have also become an important processing technology for graphene alloy materials. However, the problems of carbonization and agglomeration are prone to occur during the melting process of graphene mixed with metal.
[0004] The above information disclosed in the background technology is only used to increase the understanding of the background technology of the present application, and therefore, it may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] The invention provides a method for preparing a gold-gold nanometer highly conductive material to solve the technical problem that carbonization and agglomeration are easily generated in the existing process of mixing and melting graphene and metal.
[0006] In order to achieve the above invention / design purpose, the present invention adopts the following technical solutions:
[0007] A method for preparing a gold-encapsulated nanometer highly conductive material comprises the following steps:
[0008] Step 1, drying graphene oxide powder, aluminum powder and metal powder;
[0009] Step 2: 15-35 parts of dried graphene oxide, 50-70 parts of aluminum powder, metal powder, 0.8-1.3 parts of potassium fluorozirconate, and 0.6-1 parts of potassium fluoroborate are stirred evenly under anaerobic conditions, 20-45 parts of n-butanol are added and stirred evenly under anaerobic conditions; 0.3-1.2 parts of polyvinylpyrrolidone are added and stirred evenly under anaerobic conditions, 0.5-1.6 parts of isobutyl ether are added and stirred evenly under anaerobic conditions, and the mixture is frozen at a low temperature of -180°C to 200°C for the first time; wherein, the metal powder The powder includes: 0.05-0.09 parts of silver powder, 0.01-0.18 parts of nickel powder, 0.1-0.25 parts of magnesium powder, 0.18-0.4 parts of sodium powder, 0.15-0.22 parts of silicon powder, 0.001-0.008 parts of chromium, 0.002-000.6 parts of manganese powder, 0.03-0.06 parts of copper powder, 0.04-0.07 parts of zinc powder, 0.002-0.008 parts of rare earth powder, 0.00006-0.0001 parts of titanium, and 0.0004-0.0008 parts of iron;
[0010] Step 3, placing the pressed embryo under anaerobic conditions at room temperature for a second time, and drying the pressed embryo under anaerobic conditions to obtain a graphene mixture;
[0011] Step 4, adding 50-75 parts of aluminum particles to the graphene mixture, the aluminum particles cover the graphene mixture, gradually heating and baking, and performing the following melting and stirring cycles at least twice: stirring-heating-adding aluminum particles-keeping warm; casting to obtain graphene gold ingots; wherein the stirring directions of two adjacent cycles are opposite, and 10-20 parts of aluminum particles are added each time;
[0012] Step 5, taking 4-12 parts of aluminum ingot, 1-3 parts of gold ingot, 0.08-0.16 parts of boron, and 0.09-0.18 parts of zirconium carbide, gradually heating and baking, melting and stirring, and casting into gold nano high-conductivity catalytic module ingots to form a highly concentrated catalytic module;
[0013] Step 6: 1-3 parts of highly concentrated catalytic modules and 3-9 parts of aluminum ingots are heated to 850° C.-950° C. for melting; dehydrogenation, refining, and casting to obtain olefin gold nano-highly conductive material.
[0014] Wherein, the parts are all parts by weight.
[0015] In the method for preparing the gold-gold nano-highly conductive material as described above, in step 1, the method for drying the graphene oxide powder is: flattening the graphene oxide powder to a thickness of 3-5 mm and drying it at 110°C-130°C for 2-4 hours; the temperature for drying the aluminum powder and the metal powder is 110°C-130°C.
[0016] According to the method for preparing the gold-plated nanometer highly conductive material as described above, in step 1 and step 2, the metal powder further comprises at least one of the following metal powders: 0.002-0.008 parts of neodymium powder, 0.000005-0.000009 parts of cobalt powder, 0.0000002-0.0000007 parts of vanadium powder, 0.000008-0.000012 parts of molybdenum powder, 0.000002-0.00006 parts of niobium powder, 0.0000005-0.000006 parts of tantalum powder. 0.00000004-0.00000008 parts of palladium powder, 0.00000001-0.00000004 parts of indium powder, 0.00000008-0.00000013 parts of ruthenium powder, 0.0000000005-0.000000009 parts of tungsten powder, 0.000000002-0.000000006 parts of cerium powder, and 0.00000000002-0.0000000006 parts of yttrium powder.
[0017] In the method for preparing the gold-on-gold nanometer highly conductive material as described above, in step 2, after being stirred evenly under anaerobic conditions, ultrasonic oscillation is required for a period of time, and the first period is 28-36 hours.
[0018] In the method for preparing the above-mentioned gold-plated nanometer highly conductive material, in the step 3, the second time is 3-6 hours, the thickness during drying is 3-5 mm, the drying temperature is 110-130° C., and the drying time is 2-5 hours.
[0019] The preparation method of the above-mentioned gold nano-highly conductive material, in step 4, the gradual heating and baking process is: the first heating to 350°C-375°C for 1-2h, the second heating to 400°C-425°C for 1-2h, the third heating to 450°C-475°C for 1-2h, the fourth heating to 500°C-525°C for 1-2h, the fifth heating to 550°C-575°C for 0.5-1h, the sixth heating to 400°C-425°C for 1-2h, the sixth heating to 500°C-525°C for 1-2h, the seventh heating to 550°C-575°C for 0.5-1h, and the eighth heating to 400°C-425°C for 1-2h. Heat to 600℃-625℃ and keep warm for 0.5-1h, heat to 650℃-675℃ for the seventh time and keep warm for 0.5-1h, heat to 700℃-725℃ for the eighth time and keep warm for 0.5-1h; the melting and stirring cycle process is: stir with a spiral stirrer counterclockwise for 0.1-0.3h for the first time and then exit the spiral stirrer, heat to 750℃-775℃ for the ninth time, add 10-15 parts of aluminum particles for the first time, and keep warm for 0.1-0.2h ; Stir clockwise with a spiral stirrer for 0.1-0.2h for the second time and then exit the spiral stirrer, heat up to 800℃-825℃ for the tenth time, add 10-15 parts of aluminum particles for the second time, and keep warm for 0.15-0.3h; Stir counterclockwise with a spiral stirrer for 0.15-0.3h for the third time and then exit the spiral stirrer, heat up to 850℃-875℃ for the eleventh time, add 10-20 parts of aluminum particles for the third time, and keep warm for 0.15-0.3h, Stir clockwise with a spiral stirrer for 0.15-0.3h for the fourth time and then exit the spiral stirrer. Heat to 900℃-925℃ for the twelfth time. Add 10-20 parts of aluminum particles for the fourth time and keep warm for 0.15-0.3h. Stir counterclockwise with a spiral stirrer for the fifth time for 0.15-0.3h and then exit the spiral stirrer. Heat to 950℃-975℃ for the thirteenth time. Add 10-20 parts of aluminum particles for the fifth time and keep warm for 0.15-0.3h.
[0020] According to the method for preparing the gold-on-gold nanometer highly conductive material, after the fifth addition of aluminum particles and heat preservation, the spiral stirrer is continued to be stirred clockwise for 0.15-0.3h, and then the spiral stirrer is removed and the heat preservation is performed for 0.15-0.3h.
[0021] According to the preparation method of the above-mentioned gold-plated nanometer highly conductive material, in the step 5, the method of gradually heating up, baking, and melting and stirring is: heating to 450°C-500°C for the first time, keeping warm for 0.5-1h; heating to 600°C-650°C for the second time, keeping warm for 0.5-1h, heating to 700°C-750°C for the third time, keeping warm for 0.5-1h, stirring with a spiral stirrer counterclockwise for 0.15-0.25h and exiting the spiral stirrer, heating to 800°C-850°C for the fourth time, stirring with a spiral stirrer clockwise for 0.25-0.5h and exiting the spiral stirrer, heating to 900°C-950°C for the fifth time, stirring with a spiral stirrer counterclockwise for 0.15-0.25h and then stirring clockwise for 0.15-0.25h and exiting the spiral stirrer.
[0022] Compared with the prior art, the advantages and positive effects of the present invention are:
[0023] The method for preparing the gold-gold nanometer high-conductivity material comprises the following steps: adding potassium fluorozirconate, potassium fluoroborate, n-butanol, vinylpyrrolidone and isobutyl ether to dried graphene oxide powder, aluminum powder and metal powder in sequence, stirring the mixture evenly and then freezing the mixture; during the freezing process, graphene is better dispersed; a method of gradually heating up and baking, and multiple melting and stirring cycles is adopted to cause the mixture to roll up and down during the smelting process to achieve the purpose of even graphene adsorption, thereby greatly improving the conductivity.
[0024] After reading the specific embodiments of the present invention in conjunction with the accompanying drawings, other features and advantages of the present invention will become more clear. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 It is the gold-encapsulated nanometer highly conductive material obtained in a specific embodiment of the present invention.
[0027] Figure 2 It is the standard pull peak diagram of aluminum.
[0028] Figure 3 It is a peak diagram of a specific embodiment of the present invention.
[0029] Figure 4 This is a photo of the high-concentration catalytic module and the aluminum ingot after melting according to a specific embodiment of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the description of the present invention, it should be understood that the terms "center", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore, should not be understood as a limitation on the present invention.
[0032] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances. In the description of the implementation method, specific features, structures, materials or characteristics can be combined in any one or more embodiments or examples in a suitable manner.
[0033] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features.
[0034] In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0035] A method for preparing a gold-encapsulated nanometer highly conductive material comprises the following steps:
[0036] Step 1: Drying graphene oxide powder, aluminum powder and metal powder.
[0037] The method for drying the graphene oxide powder is as follows: spreading the graphene oxide powder to a thickness of 3-5 mm, and drying at 110° C.-130° C. for 2-4 hours.
[0038] The temperature for drying aluminum powder and metal powder is 110℃-130℃.
[0039] Step 2, 15-35 parts of dried graphene oxide, 50-70 parts of 800-1000 mesh aluminum powder, metal powder, 0.8-1.3 parts of potassium fluorozirconate, and 0.6-1 parts of potassium fluoroborate are stirred evenly under anaerobic conditions, 20-45 parts of n-butanol are added and stirred evenly under anaerobic conditions; 0.3-1.2 parts of polyvinylpyrrolidone are added and stirred evenly under anaerobic conditions, 0.5-1.6 parts of isobutyl ether are added and stirred evenly under anaerobic conditions, and frozen at a low temperature of -180°C--200°C for the first time; wherein the metal powder includes: Silver powder 0.05-0.09 parts, nickel powder 0.01-0.18 parts, magnesium powder 0.1-0.25 parts, sodium powder 0.18-0.4 parts, silicon powder 0.15-0.22 parts, chromium 0.001-0.008 parts, manganese powder 0.002-000.6 parts, copper powder 0.03-0.06 parts, zinc powder 0.04-0.07 parts, rare earth powder 0.002-0.008 parts, titanium 0.00006-0.0001 parts, iron 0.0004-0.0008 parts; metal elements have the function of adjusting the chemical composition of aluminum liquid.
[0040] In some embodiments, the metal powder further comprises at least one of the following metal powders: 0.002-0.008 parts of neodymium powder, 0.000005-0.000009 parts of cobalt powder, 0.0000002-0.0000007 parts of vanadium powder, 0.000008-0.000012 parts of molybdenum powder, 0.000002-0.00006 parts of niobium powder, 0.0000005-0.0000009 parts of tantalum powder, 0.00 0.000004-0.00000008 parts, indium powder 0.00000001-0.00000004 parts, ruthenium powder 0.00000008-0.00000013 parts, tungsten powder 0.0000000005-0.0000000009 parts, cerium powder 0.000000002-0.000000006 parts, yttrium powder 0.00000000002-0.0000000006 parts. The type of metal powder can be selected according to demand.
[0041] Among them, after being stirred evenly under anaerobic conditions, ultrasonic oscillation is required for a period of time, the first time being 28-36 hours.
[0042] Specifically, 15-35 parts of dried graphene oxide, 50-70 parts of 800-1000 mesh aluminum powder, metal powder, 0.8-1.3 parts of potassium fluorozirconate, and 0.6-1 parts of potassium fluoroborate are stirred evenly under anaerobic conditions, subjected to ultrasonic oscillation for 1h-2h, 20-45 parts of n-butanol are added and stirred evenly under anaerobic conditions, subjected to ultrasonic oscillation for 0.5h-1.5h, 0.3-1.2 parts of polyvinylpyrrolidone are added and stirred evenly under anaerobic conditions, subjected to ultrasonic oscillation for 1h-2h, 0.5-1.6 parts of isobutyl ether are added and stirred evenly under anaerobic conditions, subjected to ultrasonic oscillation for 1.5h-3h, and then placed in a nitrogen liquid tank for low-temperature freezing, and frozen at a low temperature of -180°C to 200°C for the first time.
[0043] Graphene oxide, aluminum powder, metal powder, n-butanol, polyvinylpyrrole, isobutyl ether, potassium fluoroborate and potassium fluorozirconate are synthesized and stirred evenly. The low-temperature freezing process makes the graphene thinner and easier to mix and adsorb with other elements, making the graphene better dispersed.
[0044] Step 3: Place the pressed embryo under oxygen-free and room temperature conditions for a second time, and dry the pressed embryo under oxygen-free conditions to obtain a graphene mixture, wherein the second time is 3-6 hours, the thickness is 3-5 mm during drying, the drying temperature is 110-130° C., and the drying time is 2-5 hours.
[0045] Step 4: Add 50-75 parts of aluminum particles with a diameter of 0.3-0.8 mm to the graphene mixture, cover the aluminum particles on the graphene mixture, gradually heat and bake, and perform the following melting and stirring cycles at least twice: stirring-heating-adding aluminum particles-keeping warm; filtering and casting to obtain graphene gold ingots; wherein the stirring directions of two adjacent cycles are opposite, and 10-20 parts of aluminum particles are added each time.
[0046] The gradual heating and baking process is: the first heating to 350℃-375℃ for 1-2h, the second heating to 400℃-425℃ for 1-2h, the third heating to 450℃-475℃ for 1-2h, the fourth heating to 500℃-525℃ for 1-2h, the fifth heating to 550℃-575℃ for 0.5-1h, the sixth heating to 600℃-625℃ for 0.5-1h, The seventh temperature is raised to 650℃-675℃ and kept warm for 0.5-1h, and the eighth temperature is raised to 700℃-725℃ and kept warm for 0.5-1h; the melting and stirring cycle process is: the spiral stirrer is used to stir counterclockwise for 0.1-0.3h for the first time, and then the spiral stirrer is withdrawn; the ninth temperature is raised to 750℃-775℃, 10-15 parts of aluminum particles are added for the first time, and kept warm for 0.1-0.2h; the second time is stirred with a spiral stirrer clockwise Stir for 0.1-0.2h and then exit the spiral stirrer. Heat to 800℃-825℃ for the tenth time, add 10-15 parts of aluminum particles for the second time, and keep warm for 0.15-0.3h; Stir with a spiral stirrer counterclockwise for 0.15-0.3h for the third time and then exit the spiral stirrer. Heat to 850℃-875℃ for the eleventh time, add 10-20 parts of aluminum particles for the third time, and keep warm for 0.15-0.3h. Stir with a spiral stirrer clockwise for 0.15-0.3h for the fourth time and then exit the spiral stirrer. Heat to 900℃-925℃ for the twelfth time, add 10-20 parts of aluminum particles for the fourth time, and keep warm for 0.15-0.3h. Stir with a spiral stirrer counterclockwise for 0.15-0.3h for the fifth time and then exit the spiral stirrer. Heat to 950℃-975℃ for the thirteenth time, add 10-20 parts of aluminum particles for the fifth time, and keep warm for 0.15-0.3h. After adding aluminum particles for the fifth time and keeping warm, continue to stir clockwise with the spiral stirrer for 0.15-0.3h, then withdraw the spiral stirrer and keep warm for 0.15-0.3h.
[0047] Step 5: Take 4-12 parts of aluminum ingot, 1-3 parts of gold ingot, 0.08-0.16 parts of boron, and 0.09-0.18 parts of zirconium carbide, gradually heat and bake, melt and stir, filter and cast into gold nano high-conductivity catalytic module ingots to form a highly concentrated catalytic module.
[0048] The method of gradually heating up, baking and melting and stirring is as follows: heating to 450℃-500℃ for the first time and keeping warm for 0.5-1h; heating to 600℃-650℃ for the second time and keeping warm for 0.5-1h; heating to 700℃-750℃ for the third time and keeping warm for 0.5-1h, stirring with a spiral stirrer counterclockwise for 0.15-0.25h and exiting the spiral stirrer; heating to 800℃-850℃ for the fourth time and stirring with a spiral stirrer clockwise for 0.25-0.5h and exiting the spiral stirrer; heating to 900℃-950℃ for the fifth time and stirring with a spiral stirrer counterclockwise for 0.15-0.25h and then stirring clockwise for 0.15-0.25h and exiting the spiral stirrer.
[0049] Step 6: 1-3 parts of highly concentrated catalytic modules and 3-9 parts of aluminum ingots are heated to 850° C.-950° C. for melting; dehydrogenation, refining, and casting to obtain olefin gold nano-highly conductive material.
[0050] Wherein, the parts are all parts by weight.
[0051] A method for preparing a gold-encapsulated nanometer highly conductive material comprises the following steps:
[0052] Step 1: Drying graphene oxide powder, aluminum powder and metal powder.
[0053] The method for drying the graphene oxide powder is as follows: the graphene oxide powder is flattened to a thickness of 4 mm and dried at 120° C. for 3 h.
[0054] The temperature for drying aluminum powder and metal powder is 120°C.
[0055] Step 2, 20 parts of dried graphene oxide, 60 parts of 900 mesh aluminum powder, metal powder, 1.1 parts of potassium fluorozirconate, and 0.8 parts of potassium fluoroborate are stirred evenly under anaerobic conditions, and 30 parts of n-butanol are added and stirred evenly under anaerobic conditions; 0.38 parts of polyvinylpyrrolidone are added and stirred evenly under anaerobic conditions, 1.2 parts of isobutyl ether are added and stirred evenly under anaerobic conditions, and frozen at a low temperature of -190°C for the first time; wherein the metal powder includes: 0.07 parts of silver powder, 0.09 parts of nickel powder, 0.15 parts of magnesium powder, 0.3 parts of sodium powder, 0.2 parts of silicon powder, 0.005 parts of chromium, 0.004 parts of manganese powder, 0.05 parts of copper powder, 0.05 parts of zinc powder, 0.006 parts of rare earth powder, 0.00009 parts of titanium, and 0.0006 parts of iron.
[0056] Among them, after being stirred evenly under anaerobic conditions, ultrasonic oscillation is required for a period of time, the first time being 32 hours.
[0057] Specifically, 20 parts of dried graphene oxide, 60 parts of 900-mesh aluminum powder, metal powder, 1.1 parts of potassium fluorozirconate, and 0.8 parts of potassium fluoroborate are stirred evenly under anaerobic conditions, and ultrasonically oscillated for 1.5 hours. 30 parts of n-butanol are added and stirred evenly under anaerobic conditions. After ultrasonic oscillation for 0.9 hours, 0.9 parts of polyvinylpyrrolidone are added and stirred evenly under anaerobic conditions. After ultrasonic oscillation for 1.5 hours, 1.2 parts of isobutyl ether are added and stirred evenly under anaerobic conditions. After ultrasonic oscillation for 2 hours, the mixture is placed in a nitrogen liquid tank for low-temperature freezing, and frozen at a low temperature of -190°C for the first time.
[0058] Graphene oxide, aluminum powder, metal powder, n-butanol, polyvinylpyrrole, isobutyl ether, potassium fluoroborate and potassium fluorozirconate are synthesized and stirred evenly. The low-temperature freezing process makes the graphene thinner and easier to mix and adsorb with other elements, making the graphene better dispersed.
[0059] Step 3: Place the pressed embryo under oxygen-free and room temperature conditions for a second time, and dry the pressed embryo under oxygen-free conditions to obtain a graphene mixture, wherein the second time is 5 hours, the thickness is 4 mm during drying, the drying temperature is 120° C., and the drying time is 4 hours.
[0060] Step 4: Add 60 parts of aluminum particles with a diameter of 0.5 mm to the graphene mixture, cover the aluminum particles on the graphene mixture, gradually heat and bake, and perform the following melting and stirring cycles at least twice: stirring-heating-adding aluminum particles-keeping warm; filtering and casting to obtain graphene gold ingots; wherein, the stirring directions of the two adjacent cycles are opposite, and 15 parts of aluminum particles are added each time.
[0061] The gradual heating and baking process is as follows: the first heating to 360℃ for 1.5h, the second heating to 410℃ for 1.5h, the third heating to 460℃ for 1.5h, the fourth heating to 510℃ for 1.5h, the fifth heating to 560℃ for 0.8h, the sixth heating to 610℃ for 0.8h, the seventh heating to 660℃ for 0.8h, the eighth heating to 710℃ for 0.8h; the melting and stirring cycle process is as follows: the first time the spiral stirrer is used to stir counterclockwise for 0.2h and then the spiral stirrer is withdrawn, the ninth heating to 760℃, 12 parts of aluminum particles are added for the first time and kept warm for 0.15h; the second time the spiral stirrer is used to stir counterclockwise for 0.2h and then the spiral stirrer is withdrawn, the ninth heating to 760℃, 12 parts of aluminum particles are added for the first time and kept warm for 0.15h; the second time the spiral stirrer is used to stir counterclockwise for 0.2h and then the spiral stirrer is withdrawn, the ninth heating to 760℃, 12 parts of aluminum particles are added for the first time and kept warm for 0.15h Stir clockwise for 0.15h and then exit the spiral stirrer. The temperature is raised to 810℃ for the tenth time. 12 parts of aluminum particles are added for the second time and kept warm for 0.18h. Stir counterclockwise with the spiral stirrer for 0.2h for the third time and then exit the spiral stirrer. The temperature is raised to 860℃ for the eleventh time. 15 parts of aluminum particles are added for the third time and kept warm for 0.2h. Stir clockwise with the spiral stirrer for the fourth time and then exit the spiral stirrer. The temperature is raised to 910℃ for the twelfth time. 15 parts of aluminum particles are added for the fourth time and kept warm for 0.2h. Stir counterclockwise with the spiral stirrer for the fifth time and then exit the spiral stirrer. The temperature is raised to 960℃ for the thirteenth time. 15 parts of aluminum particles are added for the fifth time and kept warm for 0.2h. After adding aluminum particles for the fifth time and keeping warm, continue to stir clockwise with the spiral stirrer for 0.2h and then exit the spiral stirrer and keep warm for 0.2h.
[0062] Step 5: Take 8 parts of aluminum ingot, 2 parts of gold ingot, 0.12 parts of boron and 0.15 parts of zirconium carbide, gradually heat and bake, melt and stir, filter and cast into gold nano high-conductivity catalytic module ingots to form a highly concentrated catalytic module.
[0063] The method of gradually heating up, baking and melting and stirring is as follows: heating to 480°C for the first time and keeping warm for 0.7h; heating to 630°C for the second time and keeping warm for 0.8h; heating to 720°C for the third time and keeping warm for 0.8h, stirring with a spiral stirrer counterclockwise for 0.2h and exiting the spiral stirrer; heating to 830°C for the fourth time, stirring with a spiral stirrer clockwise for 0.4h and exiting the spiral stirrer; heating to 930°C for the fifth time, stirring with a spiral stirrer counterclockwise for 0.2h and then stirring clockwise for 0.2h and exiting the spiral stirrer.
[0064] Step 6: Heat 2 parts of the highly concentrated catalyst module and 6 parts of the aluminum ingot to 930°C for melting; dehydrogenate, refine, and cast to obtain the gold nanoparticle highly conductive material. Figure 4 The photo shown shows a water-clear transparent body, indicating that the graphene is evenly distributed.
[0065] Wherein, the parts are all parts by weight.
[0066] pass Figure 2 and Figure 3 By comparing, we can see that Figure 2 The nature or alloy of Zhongyuan aluminum will not change during the pulling process. Figure 3 After the graphene powder is evenly dispersed, the gold nanoparticles with high conductivity appear new peaks and Figure 2 Chalco's standard peak diagram is different.
[0067] Figure 3 0914-2G is a gold-on-carbon nanometer highly conductive material produced according to the ratio of this embodiment, and 0915-1G, 0915-3G, and 0916-3 are three gold-on-carbon nanometer highly conductive materials produced according to other ratios of the present invention, for comparison.
[0068] The obtained product is Figure 1 shown.
[0069] The obtained products are tested according to the GB / T351-2019 metal material resistivity measurement method, and the product test conductivity is shown in the following table:
[0070]
[0071] In some embodiments, the metal powder further comprises the following metal powders: 0.002-0.008 parts of neodymium powder, 0.000005-0.000009 parts of cobalt powder, 0.0000002-0.0000007 parts of vanadium powder, 0.000008-0.000012 parts of molybdenum powder, 0.000002-0.00006 parts of niobium powder, 0.0000005-0.0000009 parts of tantalum powder, 0.0000 0.0004-0.00000008 parts, indium powder 0.00000001-0.00000004 parts, ruthenium powder 0.00000008-0.00000013 parts, tungsten powder 0.0000000005-0.0000000009 parts, cerium powder 0.000000002-0.000000006 parts, yttrium powder 0.00000000002-0.0000000006 parts. The type of metal powder can be selected according to demand.
[0072] The obtained products are tested according to the GB / T351-2019 metal material resistivity measurement method, and the product test conductivity is shown in the following table:
[0073]
[0074] It can be seen that the conductivity of gold nanoparticles with high conductivity is greatly improved.
[0075] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing a gold-encapsulated nanometer highly conductive material, characterized in that: The steps include: Step 1, drying graphene oxide powder, aluminum powder, silver powder, nickel powder, magnesium powder, sodium powder, silicon powder, chromium powder, manganese powder, copper powder, zinc powder, rare earth powder, titanium powder and iron powder; Step 2, 15-35 parts of dried graphene oxide, 50-70 parts of aluminum powder, 0.05-0.09 parts of silver powder, 0.01-0.18 parts of nickel powder, 0.1-0.25 parts of magnesium powder, 0.18-0.4 parts of sodium powder, 0.15-0.22 parts of silicon powder, 0.001-0.008 parts of chromium powder, 0.002-000.6 parts of manganese powder, 0.03-0.06 parts of copper powder, 0.04-0.07 parts of zinc powder, 0.002-0.008 parts of rare earth powder, 0.00006-0.0001 parts of titanium powder, 0.0004-0.0008 parts of iron powder, 0.8-1.3 parts of potassium fluorozirconate, and 0.6-1 parts of potassium fluoroborate are stirred evenly under anaerobic conditions, 20-45 parts of n-butanol are added and stirred evenly under anaerobic conditions; 0.3-1.2 parts of polyvinylpyrrolidone are added and stirred evenly under anaerobic conditions, 0.5-1.6 parts of isobutyl ether are added and stirred evenly under anaerobic conditions, and frozen at a low temperature of -180°C to 200°C for the first time; After being stirred evenly under anaerobic conditions, ultrasonic oscillation is required for a period of time; Step 3, placing the pressed embryo under anaerobic conditions at room temperature for a second time, and drying the pressed embryo under anaerobic conditions to obtain a graphene mixture; Step 4, adding 50-75 parts of aluminum particles to the graphene mixture, the aluminum particles cover the graphene mixture, gradually heating and baking, and performing the following melting and stirring cycles at least twice: stirring-heating-adding aluminum particles-keeping warm; casting to obtain graphene gold ingots; wherein the stirring directions of two adjacent cycles are opposite, and 10-20 parts of aluminum particles are added each time; Step 5, taking 4-12 parts of aluminum ingot, 1-3 parts of gold ingot, 0.08-0.16 parts of boron, and 0.09-0.18 parts of zirconium carbide, gradually heating and baking, melting and stirring, and casting into gold nano high-conductivity catalytic module ingots to form a highly concentrated catalytic module; Step 6, heating 1-3 parts of the highly concentrated catalytic module and 3-9 parts of the aluminum ingot to 850°C-950°C for melting; dehydrogenation, refining, and casting to obtain the gold nanoparticle highly conductive material; Wherein, the parts are all parts by weight.
2. The method for preparing the gold-alloy nano-highly conductive material according to claim 1, characterized in that: In the step 1, the method for drying the graphene oxide powder is: flattening the graphene oxide powder to a thickness of 3-5 mm and drying it at 110° C.-130° C. for 2-4 hours; the temperature for drying aluminum powder, silver powder, nickel powder, magnesium powder, sodium powder, silicon powder, chromium powder, manganese powder, copper powder, zinc powder, rare earth powder, titanium powder and iron powder is 110° C.-130° C.
3. The method for preparing the gold-alloy nano-highly conductive material according to claim 1, characterized in that: In step 2, the first time is 28-36 hours.
4. The method for preparing the gold-alloy nano-highly conductive material according to claim 1, characterized in that: In step 3, the second time is 3-6 hours, the thickness during drying is 3-5 mm, the drying temperature is 110-130° C., and the drying time is 2-5 hours.
5. The method for preparing the gold-alloy nano-highly conductive material according to claim 1, characterized in that: In step 4, the stepwise heating and baking process is as follows: the first heating is to 350°C-375°C and kept warm for 1-2h, the second heating is to 400°C-425°C and kept warm for 1-2h, the third heating is to 450°C-475°C and kept warm for 1-2h, the fourth heating is to 500°C-525°C and kept warm for 1-2h, the fifth heating is to 550°C-575°C and kept warm for 0.5-1h, the sixth heating is to 600°C-625°C and kept warm for 0.5-1h. The seventh time, the temperature is raised to 650℃-675℃ and kept warm for 0.5-1h. The eighth time, the temperature is raised to 700℃-725℃ and kept warm for 0.5-1h. The melting and stirring cycle process is as follows: the spiral stirrer is used to stir counterclockwise for 0.1-0.3h for the first time and then the spiral stirrer is withdrawn. The ninth time, the temperature is raised to 750℃-775℃. 10-15 parts of aluminum particles are added for the first time and kept warm for 0.1-0.2h. The second time, the spiral stirrer is used to stir counterclockwise for 0.1-0.3h. Stir clockwise with a stirrer for 0.1-0.2h and then exit the spiral stirrer. Heat to 800℃-825℃ for the tenth time. Add 10-15 parts of aluminum particles for the second time and keep warm for 0.15-0.3h. Stir counterclockwise with a spiral stirrer for 0.15-0.3h for the third time and then exit the spiral stirrer. Heat to 850℃-875℃ for the eleventh time. Add 10-20 parts of aluminum particles for the third time and keep warm for 0.15-0.3h. Stir with the spiral stirrer clockwise for 0.15-0.3h and then exit the spiral stirrer, heat to 900℃-925℃ for the twelfth time, add 10-20 parts of aluminum particles for the fourth time, and keep warm for 0.15-0.3h, stir with the spiral stirrer counterclockwise for 0.15-0.3h for the fifth time and then exit the spiral stirrer, heat to 950℃-975℃ for the thirteenth time, add 10-20 parts of aluminum particles for the fifth time, and keep warm for 0.15-0.3h.
6. The method for preparing the gold-alloy nano-highly conductive material according to claim 5, characterized in that: After adding aluminum particles for the fifth time and keeping warm, continue to stir clockwise with the spiral stirrer for 0.15-0.3h, then withdraw the spiral stirrer and keep warm for 0.15-0.3h.
7. The method for preparing the gold-alloy nano-highly conductive material according to claim 1, characterized in that: In step 5, the method of gradually heating up, baking and melting and stirring is: heating to 450°C-500°C for the first time and keeping warm for 0.5-1h; heating to 600°C-650°C for the second time and keeping warm for 0.5-1h; heating to 700°C-750°C for the third time and keeping warm for 0.5-1h, stirring with a spiral stirrer counterclockwise for 0.15-0.25h and exiting the spiral stirrer; heating to 800°C-850°C for the fourth time and stirring with a spiral stirrer clockwise for 0.25-0.5h and exiting the spiral stirrer; heating to 900°C-950°C for the fifth time and stirring with a spiral stirrer counterclockwise for 0.15-0.25h and then stirring clockwise for 0.15-0.25h and exiting the spiral stirrer.
Citation Information
Patent Citations
Preparation method for dual model-structure graphene-reinforced aluminum matrix composite
CN111996407A
Preparation method and application of graphene / aluminum composite material
CN115304438A